(untitled) (Research, Society and Development, 2025)
The Human Papillomavirus (HPV) is the main risk factor associated with cervical cancer and its identification can help in the early diagnosis of malignant neoplasms. Therefore, the objective of the work is to identify the incidence of HPV genotypes in women with cytological results of low-grade squamous intraepithelial lesion and atypical cells of undetermined significance. The study is cross-sectional and retrospective, where the results of women who underwent the genotyping test for HPV and the cytopathological examination in a private laboratory in Aracaju/SE, between January and October 2022, were analyzed. Of the 7,915 women who performed vaginal secretion collection, 53.19% (75/141) were diagnosed with LSIL and 46.81% (66/141) with ASC-US. Of the detectable results for HPV, 68.42% (26/38) were diagnosed with high-risk HPV with genotypes other than 16 and/or 18. Therefore, a higher incidence of women diagnosed with LSIL was observed, in addition to the majority did not perform the genotyping test.